Active tectonics in the Malaga Basin: evidences from morphotectonic markers (Western Betic Cordillera, Spain) - Insua-Arévalo, J.M.; Martínez-Díaz, J.J.; García-Mayordomo, J.; Martín-González, F. (Journal of Iberian Geology, 2012)
The Malaga Basin is located in the westernmost part of the Betic Cordillera. This alpine cordillera in the south of Spain is the most active region of the Iberian Peninsula. Some of the most destructive earthquakes occurred historically in Spain took place within the Malaga Basin. In this work we focus on geomorphic and morphotectonic observations in the aim of finding active tectonic structures that could be seismogenic sources. First, we study the spatial arrangement and age of the Quaternary alluvial fan system as well as the drainage pattern of the basin, followed by the analysis of the distribution of regional markers like marine erosive surfaces and the extend of Pliocene marine deposits in the Malaga Basin. The tectonic structures inferred as active by the morphotectonic analysis are grouped into four main families: N60º-85ºE folds associated with blind thrust faults, N20º-30ºE and N40º-50ºE high angle dip-slip faults, and N165º-170ºE tear faults. Finally, their seismic potential in terms of maximum moment magnitude (Mw) is assessed by means of empirical relationships, varying between 6.0 and 7.0 depending on the hypothesis considered.